Autogenic and audiovisual-self training for the biomotor abilities of professional boxers during Covid-19: A literature study - Bisa, M.; Sulaiman, I.; Junaidi; Tangkudung, J. A. P.; Dlis, F. (Solid State Technology, 2021)
Background from boxing is a popular contact sport that is in demand by many. Physical distancing and social distancing due to Covid-19 have caused various championships to be delayed due to environmental changes imposed by Covid-19. It causes the willingness and enthusiasm to practice the trainers to decrease. Physiologically, the muscles' strength and explosive power will decrease, which is preceded by a decrease in myofibrils, reduced muscle volume (disuse atrophy), stiffness, and limited motion the joints occur. A person's motor abilities will decrease after 5-7 days if they do not do the exercises as usual. Maximum strength, explosive muscle power and mental training must be appropriately trained and prepared. Methods withqualitative descriptions with literature studies which analyze various theories put forward by experts on strength, maximum strength, explosive muscle power, and anxiety which can affect the peak performance of professional boxers in achieving maximum performance. The resultis the conditions of environmental change due to the Covid-19 pandemic have forced the development of training methods and techniques through studies based on innovative, adaptive, and realistic sports science and sports technology. Conclusionprofessional boxers must maintain their motor skills and cope with stress through audiovisual training (audiovisual self-training) and autogenic training regularly and programmed. Maintaining and increasing muscle strength, muscle explosiveness, and maintaining an ideal body weight according to class in boxing are essential things besides other internal and external factors.